Synthesis of TiO2/Graphene oxide nanocomposites for their enhanced photocatalytic activity against methylene blue dye and ciprofloxacin. (15th October 2019) - Khan, Shakeel Ahmad; Arshad, Zunaira; Shahid, Sammia; Arshad, Ishwa; Rizwan, Komal; Sher, Mudassir; Fatima, Urooj
Abstract: We report the synthesis of TiO2 /Graphene oxide nanocomposites (2%, 4%, 6% and 8%) by liquid phase deposition of titania on graphene oxide (GO) nanosheets. This chemical method of synthesis was used due to hydrophobic/hydrophilic incompatibility of GO with metal oxides. The fabricated TiO2 /GO nanocomposites were successfully characterized using various diffraction, electron microscopy and spectroscopic techniques i.e. X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), Energy-Dispersive X-Ray (EDX), Ultra-Violet Visible, Diffuse Reflectance Spectroscopy (DRS) and Fourier Transform Infra Red (FTIR). Photocatalytic activity against methylene blue dye and ciprofloxacin was carried out by the synthesized nanocomposites under sun light spectrum. Results were revealed that average crystallite size (12.42 nm, and 12.50 nm) was observed for the synthesized pure TiO2 and TiO2 /GO (8%) nanocomposites respectively with crystalline nature and spherical morphology. Moreover, synthesized TiO2 /GO (8%) nanocomposites were found to have larger surface area (91.25 m 2 g -1 ) and narrow energy band-gap values (2.47 eV) than that of pure TiO2 (55.93 m 2 g -1 and 3.06 eV) respectively. Furthermore, the TiO2 /GO (8%) nanocomposites exhibited fastest and highest rate of photocatalytic degradation of methylene blue among all composites (2%, 4%, and 6%) and pure TiO2 in much reduced period. Their excellent photocatalytic activity against synthetic dye and ciprofloxacin under the spectrum of visible region was attributed to thin two dimensional sheet support, larger surface area, narrow band gap, higher adsorption capacity and good electron acceptability of GO. Hence, the fabricated nanocomponents could be proved valuable photocatalytic system to safe our environs from the intimidations of toxic waste products produced by different industries. Graphical abstract: Image 1 Highlights: We have fabricated the TiO2 /GO nanocomposites through liquid phase deposition. TiO2 /GO nanocomposites characterized by XRD, DRS, FTIR, SEM, EDX and UV–Visible spectroscopy. TiO2 /GO nanocomposites were evaluated for their potential application as photocatalyst system. TiO2 /GO nanocomposites demonstrated the significant photocatalytic activity against methylene blue & ciprofloxacin.